84.1k views
5 votes
Equation

(z + (6)/(7) ) + (2)/(14) = - 1


1 Answer

5 votes

Given:

The equation is


\left(z+(6)/(7)\right)+(2)/(14)=-1

To find:

The solution of the given equation.

Solution:

We have,


\left(z+(6)/(7)\right)+(2)/(14)=-1

It can be written as


\left(z+(6)/(7)\right)+(1)/(7)=-1


\left(z+(6)/(7)\right)=-1-(1)/(7)

Multiply both sides by 7.


7z+6=-7-1


7z+6=-8


7z=-8-6


7z=-14

Divide both sides by 7.


z=(-14)/(7)


z=-2

Therefore, the value of z is -2.

User RAZA MUSTAFA
by
5.4k points